Symptoms in supraventricular tachycardia: Is it simply a manifestation of increased heart rate?. (June 2016) - Yetkin, Ertan
Abstract: A significant proportion of patients in clinical practice may not have ECG recordings of the index tachycardia (non-documented SVT), or only have recordings of limited diagnostic value. Despite the highly specified symptomatic and ECG diagnostic criteria, diagnosis and referral for ablation treatment is not always straightforward. Although ECG based diagnostic or treatment algorithms have been well defined in literature, we need a symptom based diagnostic algorithm or scoring system in patients with suspected supraventricular arrhythmia. Individual approaches with a high suspicion index and concerning the paroxysmal nature and post attack symptoms would help us to identify patients suffering from SVT in complex cases.